COVID-19 regulations, political Institutions, and the environment - Fredriksson, Per G. (2022)
The COVID-19 pandemic was associated with short-term air quality improvements in many countries around the world. We study whether the degree of democracy and political institutions played a role. We provide novel empirical evidence from 119 countries. A given stringency of COVID-19 containment and closure policies had a stronger effect on air quality in more democratic countries, and in countries with majoritarian rather than proportional electoral rules. Our estimates suggest that the improvement in air quality was around 57% greater in majoritarian systems than in proportional systems. Confidence in government, trust in politicians, and social capital also affected outcomes.